(untitled) (Pedagogy of Higher and Secondary Education, 2022)
Particularities of the use technician and technology of bank in work on diploma. In article are considered theoretical and practical aspects of the shaping the artistic image in technician батика in process o f the execution studentgraduate o f the degree task